2019
DOI: 10.3390/atmos10040185
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic CH4 Emissions in the Yangtze River Delta Based on A “Top-Down” Method

Abstract: There remains significant uncertainty in the estimation of anthropogenic CH 4 emissions at local and regional scales. We used atmospheric CH 4 and CO 2 concentration data to constrain the anthropogenic CH 4 emission in the Yangtze River Delta one of the most populated and economically important regions in China. The observation of atmospheric CH 4 and CO 2 concentration was carried out from May 2012 to April 2017 at a rural site. A tracer correlation method was used to estimate the anthropogenic CH 4 emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In cold seasons, CH 4 emissions from natural sources in the region, such as wetlands and lakes, are negligible (Shen et al, 2014;Hu et al, 2019;Huang et al, 2019). However, during warm seasons, CH 4 emissions from wetlands and other water bodies are large and cannot be ignored (IPCC, 2001;Ding and Cai, 2007).…”
Section: A Priori Ch 4 Emission Map and Background Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In cold seasons, CH 4 emissions from natural sources in the region, such as wetlands and lakes, are negligible (Shen et al, 2014;Hu et al, 2019;Huang et al, 2019). However, during warm seasons, CH 4 emissions from wetlands and other water bodies are large and cannot be ignored (IPCC, 2001;Ding and Cai, 2007).…”
Section: A Priori Ch 4 Emission Map and Background Concentrationmentioning
confidence: 99%
“…The CH 4 emissions using a California-specific inventory were underestimated by 37% compared to top-down atmospheric inversions estimated for central California (Zhao et al, 2009). Top-down inverse approaches have also shown that emission inventories are biased low for China (Shen et al, 2014;Huang et al, 2019). However, one study found that the total CH 4 emissions estimated using an atmospheric Bayesian inversion were 29% smaller compared to EDGAR estimates in China and attributed the bias to an overestimation of CH 4 emissions from rice agriculture during the summer (Thompson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…If the emission of any of the substances is known then that of the others can be calculated from the relationship. The correlation method belongs to the "top-down" ones, and it has been widely used for a long time (see e.g., [17][18][19][20][21][22][23][24][25]). This method is especially applicable for the estimation of the anthropogenic emission in wintertime when the biological activity and photochemical production providing the natural sources of the major anthropogenically influenced greenhouse gases are low.…”
Section: Open Accessmentioning
confidence: 99%
“…Consequently, if the emission of one of the gases is known with reasonable confidence then that of the others can be calculated. Such a "top-down" atmospheric method has already been used for different substances in different parts of the world [19][20][21]23]. Figure 5 shows the correlations between the gases studied.…”
Section: Correlation Between the Ghg Concentrationsmentioning
confidence: 99%
“…Trace gases retrieved using ground-based remote sensing instruments are presented in Javed et al [12], who discuss the relationship between NO 2 and CHOCHO with different meteorological parameters and show the significant decreasing trend of these trace gases in the afternoon. Huang et al [13] analysed a correlation "top-down" procedure to estimate anthropogenic CH 4 emission using long-term atmospheric CH 4 and CO 2 concentration data. Moreover, the results were compared with the frequent "bottom-up" IPCC inventory procedure.…”
mentioning
confidence: 99%